2 MHz electrical resistance tomography for static liquid solid profile measurement - Yasmin, Abdul Wahab (2017)
Tomography is a technique used to reconstruct cross-sectional image of a pipeline for flow monitoring applications. There are several types of tomography system such as X-ray tomography, ultrasonic tomography, and electrical resistance tomography (ERT). ERT has many advantages compared to other types of tomography such as low cost, robust and no radiation. Thus, it becomes particularly suitable for industrial applications. However, it has been observed that the conventional practice of ERT through invasive sensing technique has exposed the ERT metal sensor to corrosion and limited its application because of inaccurate measurement of the data. Consequently, non-invasive ERT has also been introduced in low frequency (in kHz) applied to the ERT system. The low frequency ERT makes use of the phase-sensitive demodulation (PSD) approach and is a complicated technique to implement. Hence, the goal of this research is to design and develop a non-invasive ERT system with a high frequency (2 MHz) source. A total impedance of coupling capacitances (between metal electrode and conductive medium) series with resistance (conductive medium) for each pair of electrodes was assumed in the research. Based on the mathematical equation of the total impedance, a real part that is the resistance (conductive medium) must be larger than an imaginary part (capacitances), so that it easily to detect the concentration profile of the conductive medium. Therefore, the minimum frequency to ensure the real part is bigger than the imaginary one is 2 MHz. Simultaneously, the independent and flexible sixteen ERT electrodes designed for the system make it easier to replace and troubleshoot any problems with the sensor. In addition, the system carried out an experimental two-phase static liquid–solid regime for a linear back-projection algorithm using online configuration, with MATLAB as a software platform. It was also able to detect and visualize the non homogenous system of the two-phase regime. Later, the reconstructed image was improved using a global threshold technique through offline configuration. The experiment results indicate that it could detect obstacles in a vertical pipe with minimum 12 mm in diameter and 4.5 cm in height, and above.